Modern Challenges of Russian-Ukrainian Interstate Relations : from strategic partnership to a strategic problem - Suprun, Oleksandra (fi=Turun yliopisto|en=University of Turku|, 2017)
The following work attempts to discover challenges in Russian-Ukrainian interstate relations from the historical perspective. The paper intends to testify if this was due to the perception of Ukraine shaped among Russia's elite in that Russia and Ukraine failed to develop a strategic partnership which eventually resulted in the ongoing inter-state conflict. Establishing perceptions and goals of the states in this work allows the discovery reasons for the aggravation of relations. The author concludes that the adopted “Ukraine-Russia: Strategic Partnership” format of relations could have been interpreted by Russia as a precondition for reintegration in its sphere of influence. The paper suggests an outline of popular Russian and Ukrainian geopolitical theories assuming that Eurasianism presumed to be the foundation of Russian foreign policy towards Ukraine. Additionally, Ukrainian and Russian laws, concepts, doctrines, and other governmental documents, as well as speeches of the officials are studied in order to uncover foreign policy goals of the states. This includes establishing the significance of the Russian dimension in Ukrainian foreign policy and vice versa. Analysis of research articles and legislative acts on political and humanitarian aspects of Russian-Ukrainian relations allows identification of an ideological background for the implemented foreign policies and their consequences. The research is conducted by the means of process-tracing method around political, military and humanitarian aspects of the international relations, excluding the economic sphere. This is done with the purpose of focusing on the impact of values and perceptions in the interstate relations which allegedly are insufficiently reflected in the international economy. Summarisation of new approaches to problems arising from the evolution in the interstate relations from strategic partnership to adversarial relations between Russia and Ukraine enables the foreign policy executive agencies to identify specific objectives for the transformation of interstate relations in the region.